Electromagnetic Bandgap Structured CPW Fed Circular Monopole Antenna with Bandwidth Enhancement for Wideband Applications - Aradhyula, Raghavaraju; V Rama Krishna, T; T P Madhav, B (International Journal of Engineering and Technology, 2018)
A circular monopole antenna with coplanar wave guide feeding is constructed with the combination of Electromagnetic Band Gap structure for the improvement of bandwidth. A plus shaped defected ground is etched on the ground plane to obtain the EBG characteristics in the proposed antenna model. A complete analysis with respect to reflection coefficient, VSWR, impedance, radiation pattern, current distribution, gain and efficiency are presented in this work. The proposed model occupying the dimension of 50X50X1.6 mm on FR4 substrate with dielectric constant of 4.3. Antenna operating in the dual band of 1.5-3.6 GHz (GPS, LTE, Bluetooth and Wi-Fi applications) and 4.8-15 GHz (WLAN, X-Band and Satellite communication applications) with bandwidth of 2.1 and 10.2 GHz respectively. A peak realized gain of 4.8 dB and peak efficiency more than 80% are the key features of the current design.